Factors Regarding Adherence to Medication in Patients with Hypertension Based on Health Belief Model in the South of Kerman,Iran. in 2019 - Abbas Zangiabadi; Armita Shah Esmaili; seyed vahid ahmadi Tabatabaei; ehsan movahed; Hamideh Shankestani (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: hypertension is the most important public health problem in developing countries. It is a leading cause of stroke, kidney failure, premature death and a risk factor for cardiovascular disease. The aim of conducting this study was to investigate the factors associated medical Adherence of hypertension based on health belief model. Method: The present study was a descriptive-analytical study. A total of 403 hypertensive patients with health records were enrolled in the study. Data collection questionnaire included demographic questions and health belief model structures. Data using logistic regression analysis using software was 23 SPSS. Results:  More than half of the patients (58.8%) had poor medication adherence. Most of the subjects (87.3%) used less than three drugs. Pearson test results showed a significant relationship between drug compliance with age, education and job. Among the constructs of HBM, the highest mean was related to perceived benefits (88.93 ± 10.92) and the lowest to self-efficacy constructs (51.97 ±31.55). In the logistic regression model, three factors of awareness, guides to action and perceived barriers, confidently influence drug compliance. Conclusion: Effective interventions based on health belief model and with emphasis on raising awareness, practice guide and removing perceived barriers can increase medication adherence in patients with hypertension.